Officer perceptions of the impact of mobile broadband technology on police operations - Carter, Jeremy G. (Policing and society, 2017)
Research examining police departments' use of technology is underdeveloped relative to other areas of policing. This gap in the literature is troubling as policing models are becoming more data-driven and thus, relying more heavily on information technologies. Arguably, the most commonly utilised technology in policing practice, and examined in policing research, has been mobile computers. However, there has been little insight into the technological advancement in data communications that directly influence the functionality of mobile computers. This research seeks to inform this shortcoming by examining a police department that implemented a dedicated wireless mobile broadband system. A mixed-methods approach is employed within a medium-sized department in the northeast region of the USA. Survey data were gathered from 76 uniformed police personnel. Semi-structured interviews were conducted with key personnel to further contextualise survey results. Survey results suggest tentative support for improved time savings and execution of job tasks after the implementation of wireless broadband. Perceptions of mobile broadband impacts on information flow, quality, and accessibility appear positive. Considerations for future research and study limitations are discussed.